(untitled) (Fiep Bulletin - online, 2017)
In the early twentieth century, volleyball came to Brazil and, before the 1930s, it was also practiced by the women fromRio. This study aimed to analyze the trajectory of women’s volleyball in the social scene of the 1930s, with a configuration thatbegan to differentiate, and that might have contributed effectively to the achievement of a differentiated space for women insociety, especially in the following decades in Rio de Janeiro in the early steps of their relationship with Brazilian society. In thisway, we have chosen the city of Rio de Janeiro, in the 1930s, as we consider it has great representation in the inclusion of Riowomen in women’s volleyball, although the volleyball had not achieved its institutionalized form. In order to deepen this study, wetook descriptors for research in journals, scientific journals, books, newspapers, among others.